ANALYSIS OF PHARMING IN CYBER CRIME AND ITS IMPACT ON CUSTOMER TRUST (CASE STUDY ON BANK BRI CUSTOMERS BANDAR LAMPUNG REGIONAL OFFICE) - Ranny Caroline; Tina Miniawati Virgawenda Barusman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to determine and analyze the impact of pharming and cybercrime and to disseminate information about factors that affect customer trust in the use of mobile banking, a case study on Bank BRI, Bandar Lampung Regional Office. This study is quantitative research with a sample of 100 respondents, data collected through questionnaires using convenience sampling techniques with hypothesis testing using SmartPLS. The results of this study show that pharming and cybercrime have a positive and significant influence on customer trust. Therefore, it is hoped that financial institutions can commit to improving the security system of mobile banking applications periodically to maintain customer trust. Researchers are further expected to explore the latest techniques of pharming attacks or cybercrime as well as preventive measures that financial institutions can take.